Antimicrobial activities of Acinos rotundifolius Pers. from extracts of hypocotyl and cotyledon node induced calli - Ozdemir, Fethi Ahmet; Ortaeskinazi, Hayati (Progress in Nutrition, 2016)
In vitro callus propagation is extremely important both for generation of a plant’s secondary metabolites and for increasing production of these metabolites. This study reports a protocol for callus induction for Acinos rotundifolius Pers. hypocotyl and cotyledon node explants obtained from 10 days old in vitro grown plantlets. The calli obtained in this way are also examined for their antimicrobial activities. Callus induction was noted on all cotyledon node and hypocotyl explants. For cotyledon node explants the most productive environment in terms of callus weight was MS medium containing 0.04 mg/l TDZ + 0.2 mg/l IBA. Increase of the TDZ concentration resulted in decrease of the callus weight. For hypocotyl explants maximum callus induction in terms of callus weight was noted on MS medium containing 1 mg/l BAP + 0.5 mg/l 2,4-D. The increase of BAP concentration generally resulted in decreased callus weight. Irrespective of the source of calli, crude extracts of A. rotundifolius Pers were found very effective for inhibition of Staphylococcus aureus COWAN 1 and Bacillus subtilis var. niger ATCC 10. The inhibition zone diameter determined by agar diffusion methodology for each extract showed more activity against Bacillus subtilis var. niger ATCC 10 compared to Staphylococcus aureus COWAN 1. No antimicrobial activity was observed with methanol extracts. There is need to evaluate extracts against more types of bacteria to broaden the scope of A. rotundifolius Pers in pharmaceutical practice.